Inhibition of Mild Copper Metal Corrosion in HNO3 Medium by Acid Extract of Azadirachta Indica Seed - T. V. Sangeetha; M. Fredimoses (E-Journal of Chemistry)
Efficiency of acid extract of dry azadirachta indica seed as corrosion inhibitor for mild copper metal in various concentration of (1 N,2 N and 3N) HNO3 medium was investigated in the present study. Experimental methods include weight loss, determination of corrosion rate, inhibition efficiency and phytochemical analysis was studied. The results indicate azadirachta indica seed to be a good corrosion inhibitor of a mixed type and having efficiency as high as 95% at 1% inhibitor concentration in different time duration.